Role of wireless motility capsule in the assessment and management of gastrointestinal dysmotility in patients with diabetes mellitus. Issue 9 (26th April 2017) - Rouphael, C.; Arora, Z.; Thota, P. N.; Lopez, R.; Santisi, J.; Funk, C.; Cline, M.
Abstract: Background: Gastrointestinal (GI) dysmotility is common in diabetic patients. Wireless Motility Capsule (WMC) provides the transit profile of the entire GI tract in a single study. Factors affecting GI dysmotility and utility of WMC study are not clearly established in diabetic patients. Our aims were to study the pattern of GI dysmotility using WMC and evaluate the effect of glycemic control and presence of diabetic microvascular complications on motility impairment in diabetic patients. We also assessed the impact of WMC findings on clinical management. Methods: Retrospective chart review of all diabetic patients who underwent WMC testing at our institution from 2010 to 2015 was performed. Demographics, hemoglobinA1c levels, microvascular complications, and WMC findings were obtained. Impact of WMC on clinical management was assessed. Key Results: A total of 100 patients were included. Mean age was 45±19 years and 76% were female. Seventy‐two percentage had abnormal WMC testing, of which 29 (40%) had multiregional dysmotility. There were no significant differences in demographics, diabetic microvascular complications or hemoglobinA1c levels among patients with normal and abnormal WMC testing or among patients with isolated vs multiregional dysmotility. Information about subsequent clinical management was available for 47 patients. WMC testing was abnormal in 33 (70%) patients and treatment changes based on WMC results were made in 24 patients (73%). Conclusions & Inferences: There was no association between hemoglobinA1c levels, microvascular complications and pattern of GI dysmotility in diabetic patients undergoing WMC. WMC testing lead to management changes in approximately 75% of diabetic patients with GI dysmotility. Abstract : Wireless Motility Capsule allows the evaluation of the gastrointestinal tract of diabetic patients in a single test. Glycemic control and diabetic microvascular complications are not associated with extent of dysmotility. Wireless motility capsule testing can affect clinical decisions in patients with diabetes mellitus.